Simultaneously collecting coding and non-coding phylogenomic data using homemade full-length cDNA probes, tested by resolving the high-level relationships of Colubridae - Li, JiaXuan; Liang, Dan; Zhang, Peng (Frontiers in Ecology and Evolution, 2022)
Resolving intractable phylogenetic relationships often requires simultaneously analyzing a large number of coding and non-coding orthologous loci. To gather both coding and non-coding data, traditional sequence capture methods require custom-designed commercial probes. Here, we present a cost-effective sequence capture method based on homemade probes, to capture thousands of coding and non-coding orthologous loci simultaneously, suitable for all organisms. This approach, called “FLc-Capture,” synthesizes biotinylated full-length cDNAs from mRNA as capture probes, eliminates the need for costly commercial probe design and synthesis. To demonstrate the utility of FLc-Capture, we prepared full-length cDNA probes from mRNA extracted from a common colubrid snake. We performed capture experiments with these homemade cDNA probes and successfully obtained thousands of coding and non-coding genomic loci from 24 Colubridae species and 12 distantly related snake species of other families. The average capture specificity of FLc-Capture across all tested snake species is 35%, similar to the previously published EecSeq method. We constructed two phylogenomic data sets, one including 1,075 coding loci (∼817,000 bp) and the other including 1,948 non-coding loci (∼1,114,000 bp), to study the phylogeny of Colubridae. Both data sets yielded highly similar and well-resolved trees, with 85% of nodes having >95% bootstrap support. Our experimental tests show that FLc-Capture is a flexible, fast, and cost-effective sequence capture approach for simultaneously gathering coding and non-coding phylogenomic data sets to study intractable phylogenetic questions. We hope that this method will serve as a new data collection tool for evolutionary biologists working in the era of phylogenomics.